The therapy of idiopathic pulmonary fibrosis: what is next? - Somogyi, Vivien; Chaudhuri, Nazia; Torrisi, Sebastiano Emanuele; Kahn, Nicolas; Müller, Veronika; Kreuter, Michael (European respiratory review, 2019)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, fibrosing interstitial lung disease, characterised by progressive scarring of the lung and associated with a high burden of disease and early death. The pathophysiological understanding, clinical diagnostics and therapy of IPF have significantly evolved in recent years. While the recent introduction of the two antifibrotic drugs pirfenidone and nintedanib led to a significant reduction in lung function decline, there is still no cure for IPF; thus, new therapeutic approaches are needed. Currently, several clinical phase I–III trials are focusing on novel therapeutic targets. Furthermore, new approaches in nonpharmacological treatments in palliative care, pulmonary rehabilitation, lung transplantation, management of comorbidities and acute exacerbations aim to improve symptom control and quality of life. Here we summarise new therapeutic attempts and potential future approaches to treat this devastating disease. - Tweetable abstract ERSpublications - click to tweetThere is still no cure for IPF. Clinical trials focus on new therapeutic targets, improvements in nonpharmacological therapies and treatment of comorbidities and acute exacerbations. All future therapies should aim to reduce the burden of disease. http://bit.ly/2XdxqAP
Gesehen am 13.02.2020